2022
DOI: 10.1007/s40894-022-00195-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Intervention Programs Promoting Peer Relationships Among Children and Adolescents: Methods and Targets Used in Effective Programs

Abstract: Children’s peer relationships are crucial for their social-emotional development, mental and physical health. To identify effective strategies to facilitate peer relationships among 8–14-year-olds, a systematic review of intervention programs was conducted. Electronic databases ERIC, EMBASE, MEDLINE, PsycINFO, Cochrane Collection Library and grey literature sources were searched for intervention studies with general or clinical populations published between 2000 and 2020. Interventions had to assess quantity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…In other words, improving social-emotional skills and peer relationships is at the heart of most current childhood prevention approaches. While a considerable amount of literature focuses on social-emotional learning (SEL) programs (Durlak et al, 2022; van de Sande et al, 2019), peer relationship programs have not received the same attention (Pollak et al, 2022). Additionally, there is a lack of empirical studies on the relationship between social-emotional skills outcomes and peer relationship outcomes of universal, preventive programs.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…In other words, improving social-emotional skills and peer relationships is at the heart of most current childhood prevention approaches. While a considerable amount of literature focuses on social-emotional learning (SEL) programs (Durlak et al, 2022; van de Sande et al, 2019), peer relationship programs have not received the same attention (Pollak et al, 2022). Additionally, there is a lack of empirical studies on the relationship between social-emotional skills outcomes and peer relationship outcomes of universal, preventive programs.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…As prosocial behavior is vital for establishing friendships, social-emotional learning programs have been discussed as a means to facilitate peer relationships. Indeed, there is promising evidence regarding long-term effects of PYD interventions and school based SEL programs on peer relationships (Pollak et al, 2022). A review of programs aiming to facilitate peer relationships (Pollak et al, 2022) found preventive, universal, school-based programs to positively affect peer relationships through positive psychology, classroom interactions, mindfulness, and emotional resilience (Kozina, 2020;Maalouf et al, 2020;Lombas et al, 2019).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Psychological research in social and psychological development has drawn attention to the importance that close interpersonal relationships play in an individual's psychological safety and well-being [1][2][3]. During childhood, relationships with parents play the most important role, while social experiences with peers become more important progressively from early adolescence, where individuals spend more and more time outside the family environment, focus on their peer group, and generally make greater efforts to belong [4].…”
Section: Introductionmentioning
confidence: 99%